2011
DOI: 10.29074/ascls.24.4.227
|View full text |Cite
|
Sign up to set email alerts
|

DePEGylation Studies: PEG-RBC Stability in Conditions Consistent with Massive Transfusion

Abstract: Each year the United States population receives an estimated 12 to 14 million units of packed red blood cells (RBCs) and whole blood. 1,2 It is estimated that 33% of transfusions associated with trauma are with unmatched type O RBCs (UORBC). 3 UORBCs have been proven effective and relatively safe 3 however, by masking RBC surface antigens the risk of transfusion reaction may be further decreased. It is, therefore, important to evaluate and validate the stability of antigen masked RBCs, which may play a part in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…They found that maleimide-PEG-RBCs showed more stability than cyanuric chloride-PEGylation under multiple conditions. They also found that critical concentrations of lactic acid caused cyanuric chloride-PEG-RBC dePEGylation 47 .…”
Section: Engineered U-rbcsmentioning
confidence: 96%
“…They found that maleimide-PEG-RBCs showed more stability than cyanuric chloride-PEGylation under multiple conditions. They also found that critical concentrations of lactic acid caused cyanuric chloride-PEG-RBC dePEGylation 47 .…”
Section: Engineered U-rbcsmentioning
confidence: 96%
“…Likewise, the dependence on PEG molecular weight and architecture in masking RBC antigens is not entirely intuitive. Additionally, while amine-reactive chemistries have been most commonly explored, some evidence suggests that the maleimide linkage may be more stable under certain environments encountered during transfusion, although further study is necessary to more thoroughly characterize the properties of RBCs modified via different chemistries in vivo [86]. Similarly, in comparing linear PEG chains to highly branched polyglycerol (HPG), PEG chains formed larger exclusion zones and, consequently, masked major blood antigens better than HPGs, though the more compact HPG structure was found to be more effective than PEG at protecting certain minor antigens [84].…”
Section: Molecular Camouflage and Nano-encapsulationmentioning
confidence: 99%